Case report: Prazosin augmentation for treating comorbid treatment-resistant depression and chronic post-traumatic stress disorder - Guo, Ping; Fang, Yu; Feng, Ming; Zhao, Xudong; Wang, Shikai; Qian, Mincai; Huang, Juanjuan; Chen, Huanxin (Frontiers in Psychiatry, 2022)
Psychological trauma in childhood can lead to post-traumatic disorder (PTSD) with protracted comorbid depression, which responds poorly to conventional antidepressants. Previous studies have shown that prazosin, an α1-adrenergic receptor antagonist, can help eliminate nightmares and improve sleep quality and suicidal ideation in PTSD patients. This case report presents that prazosin had a rapid antidepressant effect in a female adolescent PTSD patient with treatment-resistant depression (TRD). Prazosin improved not only depression symptoms but also sleep quality, suicidal ideation, and cognitive function. Prazosin was well tolerated without obvious adverse effects. Our preliminary study suggests that further clinical trials are needed to determine the efficacy and safety of prazosin in treating PTSD patients with comorbid TRD.